Anti-Intellectualism in the Puritan Revolution - Solt, Leo F. (Church history, 1956)
The preachers of the New Model Army during the 1640's and 1650's engaged in a three-pronged attack upon the educated people of Puritan England, i.e., upon the clergy, the university teachers, and the lawyers. Both the Levellers and the Diggers gave strong support to this anti-professional or anti-intellectual point of view. Most of the Army preachers, especially William Dell, John Saltmarsh, Thomas Collier, Walter Cradock, and William Erbery, were purveyors of that branch of Independent Puritanism (sometimes called Antinomianism) which stressed the indwelling presence of the Holy Spirit rather than formal learning. Furthermore, despite the conclusions of R. H. Tawney about Puritanism in general, the Army preachers were generally concerned with the poor and uneducated members of society rather than the prosperous and educated. In the phraseology of H. Richard Niebuhr, they sought “the salvation of the socially disinherited.” An examination of this interest in social amelioration will help to clarify the anti-intellectual attack.